A-108 Inflammatory Biomarkers Link Perceived Stress With Metabolic Dysregulation. (17th August 2022) - Jurgens, Savana M; Prieto, Sarah; Hayes, Jasmeet P
Abstract: Objective: Psychological stress has been identified as a risk factor for several metabolic diseases, including cardiovascular disease and type II diabetes. However, the intermediate pathways underlying this relationship are not well understood. Inflammatory responses may be one process by which stress leads to metabolic dysregulation. Prior work has shown that chronic stress is associated with elevated systemic inflammation and that altered inflammatory activity contributes to the pathogenesis of metabolic disease. The current analyses tested this theory by examining inflammation as a pathway by which perceived stress affects metabolic health. Methods: Data from the Midlife in the United States Study (MIDUS) (N = 863; Mean age = 52.72) provided measures of perceived stress, inflammatory biomarkers [C-reactive protein (CRP), interleukin-6 (IL-6)] and metabolic health markers. Confirmatory factor analysis (CFA) was used to confirm the fit of a hierarchical model of metabolic dysregulation in our sample. Structural equation modeling (SEM) was used to test the assumption that stress is linked to metabolic dysregulation through inflammation. Results: The CFA of metabolic dysregulation demonstrated excellent goodness of fit [RMSEA = 0.040 (95% CI = 0.036–0.062); CFI = 0.973; SRMR = 0.082]. SEM supported the proposed model which included perceived stress, inflammation and the metabolic latent variable with age and sex as covariates [RMSEA = 0.082 (95% CI = 0.075–0.089); CFI = 0.898, SMSR = 0.085]. The indirect pathway linking stress to metabolic dysregulation via inflammation was significant [B = 0.029, z = 2.812, p < 0.01]. Conclusions: These results suggest that inflammatory biomarkers are a viable pathway for explaining how experiencing stress may result in metabolic dysregulation. Inflammatory processes may be an important target for future research investigating stress and adverse health outcomes.